If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 6 + 8(x + -9) Reorder the terms: 14 = 6 + 8(-9 + x) 14 = 6 + (-9 * 8 + x * 8) 14 = 6 + (-72 + 8x) Combine like terms: 6 + -72 = -66 14 = -66 + 8x Solving 14 = -66 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 14 + -8x = -66 + 8x + -8x Combine like terms: 8x + -8x = 0 14 + -8x = -66 + 0 14 + -8x = -66 Add '-14' to each side of the equation. 14 + -14 + -8x = -66 + -14 Combine like terms: 14 + -14 = 0 0 + -8x = -66 + -14 -8x = -66 + -14 Combine like terms: -66 + -14 = -80 -8x = -80 Divide each side by '-8'. x = 10 Simplifying x = 10
| 9x+84=180 | | f(x)=-2x^2+8x+3 | | m/-15=4 | | -27+23z=870 | | d=24/1*1/2 | | .72+.38t=3.68t-1.26 | | 5x^2-28=7 | | 80-23z=-610 | | -4x-y=-6 | | C=6/5(k-29) | | 5y-3+y+47=8y+50-4y | | 2x+8-4x=-44 | | 0.59+0.45t=1.74t-1.13 | | z=19+4x+4y | | -6y-3y+2=-6 | | g-820=176 | | y/5-4=-12 | | g=16(21) | | -6(4p+3)-36=2(3p+3) | | x^2-22=-6 | | -x-(-3)=1 | | 9x-9+8x+8= | | 0.25x-5=0.75x-12 | | q-313=525 | | C=5/2(K-14) | | 2*1+y=6 | | 5x^2-76=1544 | | 6(c-3)+7=3+c-14 | | -5+55-35=21 | | (5(x-9))/4=(4(x+9))/5 | | X^2+0.1X-0.4=0 | | -4a-3= |